2016
DOI: 10.1038/nrn.2016.43
|View full text |Cite
|
Sign up to set email alerts
|

The neuroscience of working memory capacity and training

Abstract: Working memory - the ability to maintain and manipulate information over a period of seconds - is a core component of higher cognitive functions. The storage capacity of working memory is limited but can be expanded by training, and evidence of the neural mechanisms underlying this effect is accumulating. Human imaging studies and neurophysiological recordings in non-human primates, together with computational modelling studies, reveal that training increases the activity of prefrontal neurons and the strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
359
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 448 publications
(392 citation statements)
references
References 138 publications
26
359
2
5
Order By: Relevance
“…A prominent hypothesis is that information exchange within and between networks occurs through the oscillatory synchronization of neuronal activity, such that synchronous neuronal firing binds neurons into ensembles engaged in specific computational functions (Varela et al, 2001; Fries, 2005; Womelsdorf et al, 2007; Fries, 2015; Parkin et al, 2015). Rhythmic synchrony increases network efficiency, a process thought to be particularly relevant for demanding cognitive processes such as working memory (WM) (Fries, 2005; Deco et al, 2011; Fell and Axmacher, 2011; Fries, 2015; Constantinidis and Klingberg, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…A prominent hypothesis is that information exchange within and between networks occurs through the oscillatory synchronization of neuronal activity, such that synchronous neuronal firing binds neurons into ensembles engaged in specific computational functions (Varela et al, 2001; Fries, 2005; Womelsdorf et al, 2007; Fries, 2015; Parkin et al, 2015). Rhythmic synchrony increases network efficiency, a process thought to be particularly relevant for demanding cognitive processes such as working memory (WM) (Fries, 2005; Deco et al, 2011; Fell and Axmacher, 2011; Fries, 2015; Constantinidis and Klingberg, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…These brain regions’ functional specialization and cooperation are the operating basis of working memory (Diwadkar et al, 2000; Baddeley, 2003). Moreover, studies from cognitive psychology and neuroscience have revealed that working memory training increases and decreases in task-related BOLD activity in different regions associated with increases in working memory capacity (Constantinidis and Klingberg, 2016). That is, both increases and decreases in the BOLD signal can be informative about the stimulus maintained in working memory, reflecting excitatory and suppressive responses to stimuli’s orientation and motion.…”
Section: Introductionmentioning
confidence: 99%
“…Out of children with low working memory capacity (WMC) around 80% struggle with reading, math, or both (Gathercole and Alloway 2008). As higher order functions rely on a well-functioning WM, increasing its capacity has been associated with obvious expectations and the quest to understand the extent of the potential benefits has been widely pursued and discussed (Schubert et al 2014;Titz and Karbach 2014;von Bastian and Oberauer 2014;Redick et al 2015;Shipstead et al 2010;Constantinidis and Klingberg 2016;Morrison and Chein 2010).…”
Section: Introductionmentioning
confidence: 99%